Individuals and materials in the Greco-Roman cults of Isis: agents, images, and practices : proceedings of the VIth International Conference of Isis Studies (Erfurt, May 6-8, 2013 - Liège, September 23-24, 2013) - Gasparini, Valentino; Veymiers, Richard (Brill, 2018)
"In Individuals and Materials in the Greco-Roman Cults of Isis Valentino Gasparini and Richard Veymiers present a collection of reflections on the individuals and groups which animated one of Antiquity's most dynamic, significant and popular religious phenomena: the diffusion and reception of the cults of Isis and other Egyptian gods throughout the Hellenistic and Roman worlds. These communities, whose members seem to share the same religious identity, for a long time have been studied in a monolithic way through the prism of the Cumontian category of the "Oriental religions". The 26 contributions of this book, divided into three sections devoted to the "agents", their "images" and their "practices", shed new light on this religious movement that appears much more heterogeneous and colorful than previously recognized"...
Keywords: Isis; Griechenland -- Altertum; Römisches Reich; Konferenzschrift -- 2013 -- Erfurt; Konferenzschrift -- 2013 -- Lüttich; Konferenzschrift -- 06.05.2013-08.05.2013 -- Erfurt; Konferenzschrift -- 23.09.2013-24.09.2013 -- Liège; Geschichte; Isiskult